Tourist encounters with places associated with longevity and reflections from Mediterranean blue zones: An environmental psychology and Attention Restoration Theory perspective - Christou, Prokopis A.; Pericleous, Katerina (My University, 2023)
The primary aim of this research is to investigate the previously unexplored aspects of places linked to longevity, as perceived by tourists, by using the theoretical frameworks of environmental psychology and Attention Restoration Theory. Information was extracted in the form of experiential reviews from visitors to the Mediterranean "blue zone" islands of Sardinia in Italy and Ikaria in Greece. An initial cluster analysis was conducted using an Artificial Intelligence (AI) system. Subsequently, the research team performed a thematic analysis to further explore specific predominant clusters and identify key themes that emerged within them. Findings betray the important construct of nature in places associated with longevity. The study demonstrates the significant role of the natural environment and its interconnected components as a central and largely acknowledged point of reference for tourists, even in places that boast a multitude of attractions and services beyond their natural surroundings. Furthermore, the adopted amalgamation of theoretical lens exposes the significance of visitors' "attention" in delivering insights of places. Finally, the combination of cluster and thematic analytical techniques used in this study act as a guide for further implementation by future researchers who deal with large amount of data that have nonetheless qualitative significance attached to them.
Keywords: Longevity; Environmental psychology